Educação de Jovens e Adultos: fatores e estratégias dos que permanecem e conseguem sucesso escolar - Passos, Valmir Almeida (2011)
The present research consists of investigating, describing and to analyze as the processes of permanence and pertaining to school success had been constructed, of a group of pupils of the Education of Young and Adults of the city of Francisco Morato - a city dormitory in the region metropolitan of São Paulo, that possesss one of the lowest I.D.H. (Index of Human Development) of the State - opposing the perspective that relates the E.J.A. to the evasion and the failure pertaining to school, that is frequent in such modality of education. The theoretical beddings are placed in the area of the Sociology of the Education and, to deal with the referring questions to the success and the pertaining to school longevity the popular classrooms, we will be guided by the theoretical explanations of Bourdieu (1998), Lahire (1997), Charlot (2000), among others. As Thiollent (1982), the research will be quantitative, in the profile of the citizens and qualitative in the interviews. We will work you say with them of the citizens respecting, therefore, the singularity of each one. We look for to remove of the citizens to the answers and not presenting immediately alternative of choice, for the collection of data, we will use questionnaires with questions closed and opened and half-structuralized interview and that they will make possible to better investigate the characteristics of these citizens: it s social and economic conditions and previous pertaining to school trajectory. The citizens of this research had developed strategies intra and extra-pertaining to school that had favored the permanence process, such as: a new relation with the school, the personal and familiar mobilization, and the possibility to acquire a cultural capital that makes possible social ascension and in the world of the work